(untitled) (Global Journal of Management and Business Research, 2019)
This study is conducted to examine the effect of corporate governance and intellectual capital on financial distress. Corporate governance in this study refers to the measurement of the effectiveness of the board of commissioners developed by The Indonesian Institute for Corporate Directorship (IICD) whereas Intellectual capital is proxy by using efficiency human capital, structural capital, relational capital, and capital employed. The measurement of financial distress uses the Altman Z-Score Modification Model. This research used multiple linear regression. The population is wholesale and retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX)during 2015-2017. This study used 96 observational data for 3 years. The results show Corporate Governance, Relational Capital Efficiency (RCE), and Capital employed efficiency (CEE) does not affect financial distress. However, Human Capital Efficiency (HCE), and Structural Capital Efficiency (SCE) could be affects financial distress.